Passivation of Ni-Cr and Ni-Cr-Mo Alloys in Low and High pH Sulfate Solutions. Issue 2 (16th February 2023) - Lutton, Katie; Han, Junsoo; Ha, Hung M.; Sur, Debashish; Romanovskaia, Elena; Scully, John R.
Abstract : The kinetics of passive oxide film formation, its thickening, and composition on Ni-22Cr and Ni-22Cr-6Mo wt% alloys were investigated at selected anodic potentials. Experiments were performed in acidic and alkaline sulfate environments using a number of characterization techniques including a combination of potentiodynamic polarization, on-line atomic emission spectro-electrochemistry (AESEC), in situ potentiostatic passive film growth, along with in situ neutron reflectometry (NR) and ex situ X-ray photoelectron spectroscopy (XPS). The roles of solution pH and Mo on the passivation behavior were discussed in terms of thermodynamic and kinetic factors governing passivation. The pH was found to have an impact on the relative chemical compositions of passive film of the Ni-22Cr alloy but not noticeably for the Ni-22Cr-6Mo alloy. Ni-rich films formed early during the passivation process while Cr(III) enrichment was observed at longer times, albeit less extensively than observed previously in Cl − solutions. The fraction of Cr(III) cations also increased with alloying of Mo at low and high pH demonstrating a strong effect of Mo on Cr(III) content during aqueous passivation in Ni based superalloys, however, a larger effect is seen in Cl − . This is a noteworthy finding as Mo is usually assumed to mainly influence pit and crevice stabilization.